Inflammatory Mechanisms of Organ Crosstalk during Ischemic Acute Kidney Injury - Laura E. White; Heitham T. Hassoun (International Journal of Nephrology)
Acute kidney injury (AKI) is a common complication during inpatient hospitalization, and clinical outcomes remain poor despite advancements in renal replacement therapy. AKI in the setting of multiple organ failure (MOF) remains a formidable challenge to clinicians and incurs an unacceptably high mortality rate. Kidney ischemia-reperfusion injury (IRI) incites a proinflammatory cascade and releases cellular and soluble mediators with systemic implications for remote organ injury. Evidence from preclinical models cites mechanisms of organ crosstalk during ischemic AKI including the expression of cellular adhesion molecules, lymphocyte trafficking, release of proinflammatory cytokines and chemokines, and modification of the host innate and adaptive immune response systems. In this paper, the influence of kidney IRI on systemic inflammation and distant organ injury will be examined. Recent experimental data and evolving concepts of organ crosstalk during ischemic AKI will also be discussed in detail.